The Power of Peers: Understanding the Link Between Social Support and Grit Among Working Students - Lase, Poppy Dyan Jelita; Wibowo, Doddy Hendro (Jurnal Bimbingan dan Konseling Terapan, 2024)
In the modern academic sphere, students often juggle work and studies, leading to challenges in maintaining academic progress. A key trait associated with managing these challenges is grit, defined as long-term perseverance and passion for goals. This research investigated the correlation between peer social support and grit among part-time working students in Salatiga, Central Java. Utilizing Multi-stage Snowball Sampling for participant selection, the study collected data from 120 undergraduate students, employing the Social Support Scale and the Grit Scale. Statistical analysis confirmed a significant positive relationship between peer social support and grit. Given the importance of grit in academic and professional outcomes, and the pivotal role of peer social support in cultivating it, this study underscores the need for educational interventions that enhance social support structures for part-time working students. The findings offer vital insights for educators and policymakers, advocating for the integration of peer-driven support systems in academic settings.